Kandungan Informasi Pengendalian Internal :Bukti Dari Pengungkapan Kelemahan Material - Lesmana, Budi; widiawati, santi (LPPM POLITEKNIK LP3I BANDUNG, 2024)
ABSTRACT This journal examines the information content of internal control. I use two conventional measures of information content – stock return volatility and trading volume – and find that both measures show a statistically greater event-period reaction to disclosure of a company's initial material weakness compared to non-period events. -adjacent events and against a sample of matched control companies. In a multivariate setting, I find significant and positive relationships between the material weakness variable and both measures of information content after controlling for several other event period news sources. Collectively, the evidence suggests that investors respond to the information contained in material weakness disclosures, consistent with these disclosures providing additional value-relevant news for investors to consider in making resource allocation decisions.